PENGARUH PENGGUNAAN INFORMASI AKUNTANSI MANAJEMEN, PENGETAHUAN AKUNTANSI DAN KEPRIBADIAN KEWIRAUSAHA TERHADAP KINERJA UMKM DI TEMBILAHAN - NOVRIANI SUSANTI; YUSRIWARTI YUSRIWARTI; SITI UMI HAPSARI (Fakultas Ekonomi Universitas Islam Indragiri, 2022)
This study aims to determine and empirically test the influence of the use of management accounting information, accounting knowledge and entrepreneurial personality on the performance of SMEs in Tembilahan. The sample in this study was 333 respondents, namely UMKM actors in Tembilahan. This study uses the Multiple Linear Regression data analysis method using SPSS Version 26. The results of the partial hypothesis test show that the use of Management Accounting Information affects the performance of MSMEs in Tembilahan, Accounting Knowledge affects the performance of UMKM in Tembilahan, and Entrepreneurial Personality affects the performance of UMKM in Tembilahan